2011
DOI: 10.1177/03946320110240s302
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Period: Immunological Modifications

Abstract: Surgical stress induces complex modifications in the hemodynamic, metabolic, neuro-hormonal and immune response ofthe individual. The magnitude ofthese alterations depends on preoperative events leading to surgery, the severity of surgical trauma, and also on post-operative/post-traumatic complications ("multiple hit hypothesis"). As in other conditions of tissue damage, surgery trauma is followed by an immune-inflammatory response, initiated at the site of injury by the innate immune system, followed by a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 61 publications
2
27
0
2
Order By: Relevance
“…They perform nonspecific and specific immune tasks essential for surveillance against tumors [15]. Major surgery is associated with a sustained postoperative reduction in the numbers and activity of NK cells and T lymphocyte subsets, including lymphokine-activated killer T cells [4,16,17]. This can significantly delay postoperative immune function; one study showed that T lymphocyte activation in response to mitogens may be delayed up to 1 week after surgery in patients underwent liver transplantation [18].…”
Section: Discussionmentioning
confidence: 99%
“…They perform nonspecific and specific immune tasks essential for surveillance against tumors [15]. Major surgery is associated with a sustained postoperative reduction in the numbers and activity of NK cells and T lymphocyte subsets, including lymphokine-activated killer T cells [4,16,17]. This can significantly delay postoperative immune function; one study showed that T lymphocyte activation in response to mitogens may be delayed up to 1 week after surgery in patients underwent liver transplantation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The host's immune response to tissue injury and surgery is complex and still poorly understood. It involves hemodynamic, metabolic, neuro-hormonal and immune responses of the individual (52). It is essential to determine the balance between pro-and anti-inflammatory factors and to quantify their changes over time (53).…”
Section: The Immune System Response To Surgery and Traumamentioning
confidence: 99%
“…Although intraoperative events, such as hypotension, can cause organ injury and dysfunction, other pathophysiologic mechanisms are encountered more commonly [8,9]. Major surgery provokes a stress response, initiated by direct tissue injury, inflammation, pain, anxiety, and change in body core temperature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Major surgery provokes a stress response, initiated by direct tissue injury, inflammation, pain, anxiety, and change in body core temperature [8]. As a result, changes in parasympathetic and sympathetic tone and in catecholamine release occur, giving rise to tachycardia, hypertension, and fluid shift.…”
Section: Introductionmentioning
confidence: 99%